THE LABOUR MARKET IMPACT OF THE UK DISABILITY DISCRIMINATION ACT: EVIDENCE FROM THE REPEAL OF THE SMALL FIRM EXEMPTION - Melanie Jones (Bulletin of Economic Research, 2008)
This paper uses data from the Quarterly Labour Force Survey in the UK (1997–2006) and changes in the coverage of the Disability Discrimination Act (DDA), that result from the removal of the small firm exemption, to assess the labour market impact of the legislation. The data support a narrowing of the employment gap between the disabled and non-disabled over the post DDA period. However, the evidence based on small firms does not support this being a direct result of the employment provisions of the DDA.